Estrutura e interação entre vegetação e ambiente de uma floresta ombrófila densa das terras baixas, Espírito Santo - Moreau, Julia Siqueira (2014)
The objective of this study was to determine the structure and species composition of shrub-tree community of a forest fragment in Lowlands Rain Forest and verify the interaction of vegetation with environmental variables. 24 plots (20 x 20 m) were marked, totaling 0.96 ha, in which were measured every shrub-trees individuals with diameter at breast height = 2.5 cm. In addition, was calculated the percentage of canopy openness through hemispherical photographs and were performed the chemical characterization of the surface soil layer (0-5 cm). The data were correlated with the absolute density of 25 species that had at least 30 individuals (obtained from the phytosociological analysis) through Canonical Correspondence Analysis. 4,585 individuals were recorded and 379 species were identified, distributed in 195 genera and 66 botanical families. The density was 4,604 ind./ha and basal area was 31.88 m²/ha. The Shannon index (H') found in this study was 5.41 and evenness (J) was 0.83, suggesting the high floristic diversity of the fragment and its similarity with preserved areas of Atlantic Forest. The most remarkable species in Importance Value (IV) was Actinostemon klotzschii (Didr.) Pax, mainly due to density and frequency. Were predominant Late Secondary species (51,9%) and zoochoric dispersion (72.3%), indicating that the studied fragment is in good condition. From the Canonical Correspondence Analysis was possible to prove that the variables phosphorus, magnesium, organic matter, nitrogen, potassium and canopy openness influenced the distribution of species on this fragment (p <0.05), especially for Xylopia frutescens Aubl. that showed high correspondence with the percentage of canopy openness and the Actinostemon klotzschii (Didr.) Pax, Chrysophyllum lucentifolium Cronquist, Ecclinusa ramiflora Mart., Eugenia platyphylla O.Berg and Rinorea bahiensis (Moric.) Kuntze that developed in places with less nutrients. Based on the foregoing, it can be concluded that the vegetation has high species richness and the environmental variables influence on the distribution of species of this fragment indicating the possibility of implantation of these species in places with higher exposure to light and low fertility.